Stem cell therapy offers new hope for the treatment of Alzheimer’s disease - He, Guodong; Huang, Jingnan; Zeng, Zhaodi; Sun, Huiyu; Wu, Chao; Xu, Qi; Hu, Chuanchen; Jin, Bei; Tong, Minfeng; Wang, Chengde (Frontiers in Cell and Developmental Biology, 2025)
Alzheimer’s disease (AD) is a progressive neurodegenerative disorder primarily characterized by memory impairment and cognitive decline, for which no curative treatment is currently available. Existing therapeutic strategies, such as cholinesterase inhibitors and N-methyl-D-aspartate (NMDA) receptor antagonists, can only provide limited symptomatic relief and fail to halt disease progression. In recent years, stem cell therapy has emerged as a promising approach for AD due to its multifaceted mechanisms of action. The therapeutic effects of stem cells in AD are mainly attributed to their ability to differentiate into functional neurons or glial cells, thereby replacing damaged cells and repairing neural networks. In addition, stem cells secrete neurotrophic and anti-inflammatory factors that contribute to the improvement of the brain microenvironment. Furthermore, they can regulate neuroinflammation, promote the clearance of β-amyloid (Aβ) deposits, and suppress neuroinflammation, thus potentially slowing disease progression. However, several challenges remain, including low cell survival rates, immune rejection, tumorigenic risks, and difficulties in crossing the blood-brain barrier. Looking ahead, the integration of advanced technologies such as organoid models, gene editing, artificial intelligence, and multi-omics approaches may drive substantial progress in the clinical translation of stem cell therapies for AD. Although still in its early stages, the future of this therapeutic strategy holds great promise.